¿Un mundo feliz?: bienestar subjetivo en Lima Metropolitana - Kelez, Dusko (2009)
The economy has put aside the quest to understand the subjective welfare of man. With the aim of recovering part of the ground the economy has lost for so many years, this research tries a response to issues about the determinants of subjective well-being using economic tools. In particular, it is desired to know to what extent the objective variables that are typically used to measure the performance of a society are really a proxy for the well-being of the population. In this sense, the paper also seeks to establish possible differences in the welfare scheme between Socioeconomic Levels (NSE). The central hypothesis is that, contrary to what it is usually assumed, improvements in objective variables (salary, employment, inflation, etc.) report no significant impact on the level of well-being of the population of Lima Metropolitana. These impacts, however, tend to be higher as socioeconomic conditions worsen. The work has two approaches. First, it uses an econometric approach using amodel based on information obtained between 1994 and 2008 about level of satisfaction of the citizens. Secondly, focus group dynamics take place segmented by socioeconomic status in order to obtain a more qualitative approach to the determinants of welfare. Among its key findings, the paper shows that less than one third of subjective well-being in Lima is explained bythe objective variables evaluated. For most NSE, real wages, prices and performance of institutions are the most important variables in their wellbeing, but nevertheless, the impact of changes on these variables decrease as socioeconomic conditions improve.